Bridgerton : The Duke and I - Book 1 Book 1 - Quinn, Julia, 1970-; Pottinger, Julie Cotler (New York, NY : Avon Books, an imprint of HarperCollinsPublishers, 2020)
"The rakish Duke of Hastings will stop at nothing to hold the marriage-mongers and matchmakers of his town at bay, even if it means pretending to be engaged to the lovely Daphne Bridgerton, but strong feelings soon intervene on both sides of this convenient arrangement"--
"Originally published as The duke and I."
"Inspiration for the Netflix original series Bridgerton"-- Cover.
Keywords: Man-woman relationships -- Fiction; Mate selection -- Fiction; Marriage -- Fiction; Nobility -- Fiction; Aristocracy (Social class) -- England; Fiction; England -- Social life and customs -- 19th century; Fiction; Historical romance